2007
DOI: 10.2147/tcrm.2007.3.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of levosulpiride in the treatment of dysmotility-like functional dyspepsia

Abstract: Abstract:The objective of this study was to assess the effectiveness and safety of levosulpiride in patients with dysmotility-like functional dyspepsia including nonerosive reflux esophagitis in conditions of daily practice. The study was conducted as a prospective, open-label, multicenter design in 342 patients with dysmotility-like functional dyspepsia (n=279) and nonerosive reflux disease (n=63), who received levosulpiride 25 mg 3 times daily orally for 4 weeks. Individual symptoms (pain/discomfort, fullnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…13,14 In this study, we found another finding that statistically significant improvement in symptom score occurred in Placebo group also. This result was supported by Fermin Mearin et al study, which has found that symptomatic response to Placebo is substantial in functional dyspepsia and clinical improvement might occur independently of detectable changes in the gastroduodenal motor activity or gastric hypersensitivity.…”
Section: Resultssupporting
confidence: 65%
“…13,14 In this study, we found another finding that statistically significant improvement in symptom score occurred in Placebo group also. This result was supported by Fermin Mearin et al study, which has found that symptomatic response to Placebo is substantial in functional dyspepsia and clinical improvement might occur independently of detectable changes in the gastroduodenal motor activity or gastric hypersensitivity.…”
Section: Resultssupporting
confidence: 65%
“…16 Levosulpiride, as a gastroprokinetic agent, has shown promising results in the treatment of various gastric disorders such as functional dyspepsia and non-erosive reflux disorder. 17 Chemically, it is a synthetic benzamide derivative with a strong inhibitory effect on dopaminergic D 2 receptors both in the central nervous system and in the GIT. 18 Studies have shown Levosulpiride to be effective in the treatment of various diseases such as dyspepsia (functional or organic), diabetic gastroparesis, reflux esophagitis, iatrogenic emesis induced by drugs such as chemotherapy, calcitonin, and anesthetics, as well as noniatrogenic nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…22 This property, together with antagonism at D2 receptors, may contribute to its gastrointestinal prokinetic effect. 17 In a randomized, double-blind trial, it was found that Levosulpiride had a similar effect to cisapride in the treatment of dysmotilitylike functional dyspepsia. 23 The drug is given mostly at the dosage of 25-50 mg three times a day because of its short half-life, which leads to poor treatment adherence by patients and adverse drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pantoprazole sodium (PNT) is a sodium 5-(difluoromethoxy)-2-[[ (3,4-dimethoxy]-2-pyridinyl) methyl]sulfinyl]-1H-benzimidazole [1] (Figure 1); it is a proton pump inhibitor drug used for short-term treatment of erosion and ulceration of the esophagus caused by gastroesophageal reflux disease [2]. It has molecular formula C 16 H 14 F 2 N 3 NaO 4 S with molar mass 405.36 g/mol [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is an atypical neuroleptic (S)-enantiomer of sulpiride having molecular formula C 15 H 23 N 3 O 4 S with molar mass 341.43 g/mol. Levosulpiride is also claimed to have mood elevating property and used in the treatment of psychoses [3], particularly negative symptoms of schizophrenia, anxiety disorders, dysthymia, vertigo, dyspepsia, irritable bowel syndrome, and premature ejaculation [4].…”
Section: Introductionmentioning
confidence: 99%